PENGGUNAAN ASAS AUDI ET ALTERAM PARTEM DALAM PROSES PERSIDANGAN GUGATAN SEDERHANA DI PENGADILAN NEGERI - Muh. Caesar Fachreza Harla; Andi Tenri Famauri; Andi Syahwiah A. Sapiddin (Collegium Studiosum Journal, 2023)
This research aims to analyze the application of the principle of audi et alteram partem in the proceedings of simple claims in the District Court and to examine the constraints and obstacles in applying the principle of audi et alteram partem in the proceedings of simple claims in the District Court. The research method used in this study is empirical research, which involves collecting data directly through field studies conducted at the District Court of Makassar and the District Court of Sungguminasa. Data collection techniques include interviews and literature review, followed by qualitative analysis and descriptive presentation. The results of this study indicate that: 1) The principle of audi et alteram partem applies to the proceedings of simple claims. Although the proceedings of simple claims are specifically regulated in the Supreme Court Regulation No. 2 of 2015 concerning Simple Justice in the General Judiciary, this principle must still be upheld. In the proceedings of simple claims, both the plaintiff and the defendant have the opportunity to express their opinions before the judge makes a decision. Parties who are absent in the first hearing will be summoned again to attend the second hearing in order to listen to arguments from the other party. 2) The constraints in applying the principle of audi et alteram partem include time limitations in the proceedings of simple claims, which may not provide sufficient time for the parties involved to present their arguments comprehensively and clearly, lack of legal support, making it difficult for them to effectively present their arguments, and lack of strong evidence, making it difficult for the judge to make accurate decisions.